2020
DOI: 10.1177/1468017320949361
|View full text |Cite
|
Sign up to set email alerts
|

Working conditions and wellbeing in UK social workers

Abstract: Summary UK social workers are exposed to chronically poor working conditions and experience extremely high levels of sickness absence. The aim of this study was to gain an in-depth understanding of working conditions and wellbeing of social workers. Seven UK social work employers sent a survey of working conditions, wellbeing, and turnover intentions to all child and family social workers, followed by a series of individual semi-structured interviews with respondents. Data were collected between January and Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Other health and social care occupations in the UK, such as social workers, were also reported to be experiencing high levels of work-related stress prior to the outbreak of COVID-19 [ 14 , 15 ]. Research on social care workers’ or support workers’ wellbeing in the UK is limited, but suggests that factors such as low pay, insecure ‘zero-hour’ contracts, and poor work–life balance are significant stressors in this workforce [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other health and social care occupations in the UK, such as social workers, were also reported to be experiencing high levels of work-related stress prior to the outbreak of COVID-19 [ 14 , 15 ]. Research on social care workers’ or support workers’ wellbeing in the UK is limited, but suggests that factors such as low pay, insecure ‘zero-hour’ contracts, and poor work–life balance are significant stressors in this workforce [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The shorter version was chosen because it has similar psychometric properties to the 35-item measure but is quicker to complete, has been used in wide-ranging studies with UK social workers (e.g. Ravalier et al, 2020aRavalier et al, , 2020c and has UK-based scoring norms. Responses are given on a 5-point Likert-type scale ranging from 1 (never) to 5 (always) in the first 15 questions, and 1 (strongly disagree) to 5 (strongly agree) for the remaining 10.…”
Section: Methodsmentioning
confidence: 99%
“…Social workers play a key role in the lives of some of the most vulnerable and disadvantaged people across the globe (Ravalier et al, 2020c). They are an essential component of a thriving economy, and research has demonstrated that for each dollar spent on social services there is at least a three dollar return to the economy.…”
mentioning
confidence: 99%
“…There is no shortage of evidence to back up this perspective. Social workers consistently rate their working conditions as some of the worst in the country (Ravalier, 2017; Ravalier and Biochat, 2018; UNISON, 2019; Ravalier et al, 2020). These studies also consistently find high numbers of social workers planning to imminently leave their jobs, anywhere from 38% on the low side (Ravalier et al, 2020) to 56% on the high side (UNISON, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Social workers consistently rate their working conditions as some of the worst in the country (Ravalier, 2017; Ravalier and Biochat, 2018; UNISON, 2019; Ravalier et al, 2020). These studies also consistently find high numbers of social workers planning to imminently leave their jobs, anywhere from 38% on the low side (Ravalier et al, 2020) to 56% on the high side (UNISON, 2019). At the same time rising poverty levels (Alston, 2019) and persistent inequality (House of Commons Library, 2020) are exacerbating the need for social work services and the complexity of the issues encountered by professionals.…”
Section: Introductionmentioning
confidence: 99%